Live news entries from the point of view of their objectivity - Danielova, Katerina (Bohemica Olomucensia, 2013)
The paper deals with the live news entries in the Czech television and the Nova television. Author compares the form of the live news entries in both televisions and evaluates their participation on the reality construction. For this purpose the author analyses the language forms used in the both news programmes from the point of view of objectivity.